Identifikasi Musculoskeletal Disorder dan penilaian postur kerja pada Pekerja Loader Semen di PT Swabina Gatra - nilamsari, neffrety; Innafin, Fatimah (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2022)
Background: Musculoskeletal disorders (MSDs) are complaints in the form of pain or tenderness, especially in the spine and waist that is felt by a person ranging from very mild complaints to very sick as a result of his work. Loader (transfer) cement is the process of transferring cement from the conveyor to the transport truck. Cement moving jobs with a long standing posture can be at risk of developing MSDs. Purpose: This study aims to identify the risk of MSDs based on subjective complaints (NBM) felt by workers and work posture analysis (REBA). Method: Respondents of this study were 3 cement loader workers shift 1 plant 2 PT Swabina Gatra. The research was conducted by observation and analyzed descriptively. The variables of this study are subjective complaints felt by respondents during work and work posture. Result: In subjective complaints (NBM), there were 2 respondents with a high level of complaints and 1 respondent with a moderate level of complaints with an average level of complaints of very pain in the left shoulder, right shoulder, upper right arm and waist. Work posture analysis (REBA) is in the very high risk category. Conclusion: Complaints of musculoskeletal disorders of cement loader workers in the category of high risk level and medium risk level. The results of the work posture analysis are included in the very high risk category. The recommendation is a change in the way of working, namely manual cement transfer to using a machine (semi-automatic system) to reduce the workload. Appeal for workers to stretch between working hours and regular exercise to prevent and reduce the risk of ergonomic factors.